Opposing effects of hypoxia on catecholaminergic locus coeruleus and hypocretin/orexin neurons in chick embryos. Issue 10 (30th April 2014) - Landry, Jeremy P.; Hawkins, Connor; Wiebe, Sabrina; Balaban, Evan; Pompeiano, Maria
ABSTRACT Terrestrial vertebrate embryos face a risk of low oxygen availability (hypoxia) that is especially great during their transition to air‐breathing. To better understand how fetal brains respond to hypoxia, we examined the effects of low oxygen availability on brain activity in late‐stage chick embryos (day 18 out of a 21‐day incubation period). Using cFos protein expression as a marker for neuronal activity, we focused on two specific, immunohistochemically identified cell groups known to play an important role in regulating adult brain states (sleep and waking): the noradrenergic neurons of the Locus Coeruleus (NA‐LC), and the Hypocretin/Orexin (H/O) neurons of the hypothalamus. cFos expression was also examined in the Pallium (the avian analog of the cerebral cortex). In adult mammalian brains, cFos expression changes in a coordinated way in these areas. In chick embryos, oxygen deprivation simultaneously activated NA‐LC while deactivating H/O‐producing neurons; it also increased cFos expression in the Pallium. Activity in one pallial primary sensory area was significantly related to NA‐LC activity. These data reveal that at least some of the same neural systems involved in brain‐state control in adults may play a central role in orchestrating prenatal hypoxic responses, and that these circuits may show different patterns of coordination than seen in adults. © 2014 Wiley Periodicals, Inc. Develop Neurobiol 74: 1030–1037, 2014